Regenerative therapy for the nonhealing cutaneous wounds - Orlovska, I.V.; Yakovenko, I.O.; Haidak, A.H.; Zmejkoski, D.Z.; Kozyrovska, N.O. (Вiopolymers and Cell, 2018)
Regenerative medicine inspired by current advances in cellular biology, genetic engineering, synthetic biology, material sciences etc. is now making resistant diseases curable. Nowadays, chronic wound healing is possible due to cell-based regenerative technologies and recent non-cell therapeutic approaches. Here we review clinical applications of human stem cells, as well as cellular and tissue products as alternatives to the traditional therapy of nonhealing wounds. The cell-based technologies for tissue regeneration and bioengineering utilize stem cells that are either injected into blood stream or directly into the target area. Cell-free regeneration technologies require either stem cell products, i.e., secretomes or their separate components, extracellular membrane vesicles, or tissue products. The stem cell therapies are designed to replace critically absent components of wounded or degenerative tissue. The stem cell secretome can promote the repair of damaged tissues independently of parent cells. Extracellular membrane vesicles mimic and recapitulate the mechanisms of stem cells in tissue regeneration and therefore might be promising for chronic wound and severe burns healing. The tissue products traditionally remain efficient wound healing remedies along with emerging advanced technologies